Decellularized kidney capsule as a three-dimensional scaffold for tissue regeneration - Khazaei, Mohammad Rasool; Ibrahim, Rawa; Faris, Rayan; Bozorgi, Azam; Khazaei, Mozafar; Rezakhani, Leila (Cell and tissue banking, 2024)
Tissue regeneration is thought to have considerable promise with the use of scaffolds designed for tissue engineering. Although polymer-based scaffolds for tissue engineering have been used extensively and developed quickly, their ability to mimic the in-vivo milieu, overcome immunogenicity, and have comparable mechanical or biochemical properties has limited their capability for repair. Fortunately, there is a compelling method to get around these challenges thanks to the development of extracellular matrix (ECM) scaffolds made from decellularized tissues. We used ECM decellularized sheep kidney capsule tissue in our research. Using detergents such as Triton-X100 and sodium dodecyl sulfate (SDS), these scaffolds were decellularized. DNA content, histology, mechanical properties analysis, attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR), biocompatibility, hemocompatibility and scanning electron microscope (SEM) imaging were measured. The results showed that the three-dimensional (3D) structure of the ECM remained largely intact. The scaffolds mentioned above had several hydrophilic properties. The best biocompatibility and blood compatibility properties were reported in the SDS method of 0.5%. The best decellularization scaffold was introduced with 0.5% SDS. Therefore, it can be proposed as a scaffold that has ECM like natural tissue, for tissue engineering applications.